Combined analysis of blood ammonia and lactate levels as a practical tool to assess the metabolic response to training sessions in male and female sprinters - Kantanista, A.; Kusy, K.; Pospieszna, B.; Korman, P.; Wielinski, D.; Zielinski, J. (The Journal of Strength and Conditioning Research, 2021)
Previous research has mainly focused on blood ammonia and lactate concentration changes in response to exercise in laboratory settings. The aim of this study was to present a combined analysis of blood ammonia and lactate levels obtained during various training sessions performed under real training conditions. Differences between the sexes were also analyzed. The study subjects included 9 male and 8 female sprinters competing at the international level. The two-way analyses of variance, with repeated measures (time × sex), for lactate and blood ammonia concentrations during strength, speed (only lactate), speed with baton exchange, and speed endurance training sessions were significant. Blood ammonia and lactate levels obtained during repeated sprints were higher in male than female athletes. Peak lactate concentrations obtained from different training sessions were different in the female (F(3, 18) = 49.82, p = 0.001, Eta2 = 0.893) and male (F(3, 21) = 312.26, p = 0.001, Eta2 = 0.978) athletes; post hoc analyses of the men and women showed differences in maximum lactate concentration between training sessions, except in the speed and strength sessions. Peak ammonia concentrations obtained in the different training sessions were also different in the female (F(3, 18) = 121.06, p = 0.001, Eta2 = 0.953) and male (F(3, 21) = 196.04, p = 0.001, Eta2 = 0.965) athletes; in both the men and women, significant differences in maximum blood ammonia concentrations were found between the training sessions, except for the speed and speed with baton exchange training sessions. The results of this study indicate that the combined analysis of lactate and blood ammonia concentration provides the coach with valuable additional information about the level of adenosine triphosphate breakdown, the energy system contribution involved in muscle energy coverage during very short, repeated maximal sprints, and, most importantly, allows the coach to check whether preworkout goals were actually met.